Real-world anti-amyloid therapy beyond traditional symptomatic populations: a longitudinal case series - Jayoung Han; Yuan Fang; Darlingtina Esiaka; Olufunmilola Abraham (Frontiers in Psychiatry, 2026)
Introduction Anti-amyloid monoclonal antibodies are approved as disease-modifying therapies for early Alzheimer’s disease (AD), but real-world evidence remains limited, particularly among individuals treated during preclinical or minimally symptomatic stages. This study characterized clinical and biomarker trajectories among anti-amyloid therapy recipients across disease stages. Method We conducted a longitudinal retrospective case series of three biomarker-positive individuals from the Alzheimer’s Disease Neuroimaging Initiative who received lecanemab or donanemab. Clinical, cognitive, cerebrospinal fluid, plasma biomarker, and amyloid PET data were examined. Results In all three cases, most of the observation period preceded anti-amyloid therapy initiation. Clinical trajectories varied by biomarker profile and treatment timing. Two participants received donanemab while cognitively normal or at an early transitional stage despite persistent amyloid- and tau-positive profiles. One participant received lecanemab after clinically significant impairment emerged. Cases 1 and 2 showed prolonged preservation of cognitive and functional performance despite sustained AD biomarker abnormalities and amyloid PET positivity. In case 2, age- and education-adjusted Wechsler Logical Memory testing detected progression to mild cognitive impairment despite preserved Mini-Mental State Examination and Clinical Dementia Rating scores. In contrast, case 3 showed persistent cognitive impairment and progression toward mild dementia. Conclusion: This case series illustrates substantial heterogeneity among real-world anti-amyloid therapy recipients. Persistent biomarker abnormalities may precede clinical decline for years, especially among highly educated individuals with substantial cognitive reserve. Conventional global screening tools may underestimate early decline and affect treatment eligibility decisions. Although not generalizable, these observations underscore the need for larger real-world studies characterizing clinical trajectories following anti-amyloid therapy.